Efek cahaya LED merah dan biru pada pertumbuhan, hasil dan kandungan klorofil tanaman pakcoy (Brassica chinensis L.) dalam Growbox - Rosyida; Karno Karno; Fajrin Pramana Putra; Julian Christopher Limantara (Fakultas Pertanian Universitas Yudharta Pasuruan, 2022)
Introduction: Light-emitting diodes (LEDs) are artificial light sources that have been widely used in indoor farming systems. The light quality of red and blue LEDs plays a role in plant growth and diverse physiological responses. The right ratio of red and blue LEDs is expected to increase the growth, yield and physiology of Pakchoy plants. Experiments on the effect of LED light quality on growth, yield and physiology of Pakchoy plants have been carried out at the Grow Box. Methods: The experiment was arranged in a Completely Randomized Design (CRD) consisting of 5 types of LED light quality, with the ratio of Red and Blue light (R:B), namely: (R10), (B10), (R5:B5), (R3:B7) , and (R7:B3). Each treatment was repeated 3 times, so there were 15 experimental units. Parameters observed included growth, yield and physiological components related to photosynthesis, namely: plant height (cm), plant length (cm), number of leaves (plant-1), leaf area (cm2), plant fresh weight (g plants -1), content of chlorophyll a, b and total (mg g-1), leaf carotenoids content (mg g-1), chlorophyll content of SPAD (Soil Plant Analysis Development), and DCGI (Dark Color Green Index). Results: The light quality of monochromatic blue LEDs (B10) and the combination of red and blue (R3:B7, R5:B5 and R7:B3) significantly improves vegetative growth, chlorophyll content, carotenoids and fresh weight than monochromatic red light (R10). Monochromatic red light R10 decreased growth, chlorophyll component and yield in Pakchoy plants. Conclusion: Red and blue LEDs with a ratio of R3:B7 showed the best results on all observation parameters.